' … breaks down silos': allied health clinicians' perceptions of informal interprofessional interactions in the healthcare workplace. Issue 1 (2nd January 2022) - King, Olivia; Shaw, Nicole
ABSTRACT: Informal interprofessional interactions have gained interest in recent interprofessional care, education, health services and social sciences research literature. Some of the established benefits associated with these interactions include enhanced communication, teamwork, research translation and the provision of safer care. Limited evidence about how informal interprofessional interactions are perceived by the allied health workforce, exists. The survey conducted at a large Australian health service explored allied health clinicians' perceptions of the benefits, challenges and enablers of informal interprofessional interactions and their recommendations to improve opportunities for these workplace interactions. Sixty-four responses were analysed descriptively (for close-ended questions) and using a framework analysis approach, informed by Bourdieu's social space theory (for open-ended questions). Perceived benefits were aligned with three themes: teams and organisations, individual clinicians and service-users. Challenges to, and enablers of, informal interprofessional interactions were identified according to five themes: socio-cultural practices, physical environment, timing-related factors, individual and organisational factors. Participant recommendations to increase opportunities for informal interprofessional workplace interactions for allied health reflected three of the aforementioned themes: socio-cultural practices, physical environment and organisational factors. This theoretically-informed analysis may aid in the development of strategies to support these types of workplace interactions and realise the benefits identified.